Reduction of the sound power radiated by a two pistons system located near the three-wall corner - RDZANEK Jr., Wojciech P.; SZEMELA, Krzysztof (Archives of Acoustics, 2007)
The main aim of this study is to calculate magnitudes describing the sound radiation by a system containing two vibrating circular pistons located in tree-wall corner. It is assumed that there is no influence of the surrounding medium on the sources vibrations and the vibration velocities of the pistons are time-harmonic.Making use of the known form of the Green function valid for tree-wall corner area the formulae presenting the acoustic pressure radiated by considered sources has been obtained. In order to characterize the sound radiation of the examined system of sources the self and the mutual powers in the integral form have been also expressed. Employing the well known integral expressions the obtained formula for the self power can be presented in the form of the fast convergent sum. The investigations presented herein can be very useful for a projection systems containing some vibrating pistons. On the basis of the presented in this paper formulae the acoustic properties of the vibrating pistons embedded in tree-wall corner can be predicted. It can be very advantageous to design vibrating systems and helpful to reduce harmful noise.